Research review on time series forecasting of gold price movement - Goh, Wesley Yi Yong; Sufahani, Suliadi Firdaus (International Journal of Multidisciplinary Research and Development, 2018)
This paper propose different techniques used in forecasting on time series analysis. Various techniques had been used in the field of time series forecasting from the traditional Box-Jenkins approach to the most popular neural network technique nowadays. However, there is no specifically the best method to deal with time series forecasting as the application of different time series forecasting methods has their own requirements and restrictions. In determining the movement of gold price, there are a lot of different methods being implemented by various authors to propose their models. Various time series forecasting method have been discussed in this paper which consists of several journal articles that related to gold price and some of the data mining techniques in time series forecasting retrieved from Google Scholar in this review.